Epidemiology and clinical characteristics of posttraumatic hospitalized patients with symptoms related to venous thromboembolism: a single-center retrospective study - Hyung Su Park; Sung Youl Hyun; Woo Sung Choi; Jin-Seong Cho; Jae Ho Jang; Jea Yeon Choi (Journal of Trauma and Injury)
Purpose The aim of this study was to investigate the epidemiology of trauma inpatients with venous thromboembolism (VTE) symptoms diagnosed using computed tomographic angiography (CTA) in Korea. Methods In total, 7,634 patients admitted to the emergency department of Gachon University Gil Medical Center, a tertiary hospital, and hospitalized between July 1, 2018 and December 31, 2020 were registered for this study. Of these patients, 278 patients who underwent CTA were enrolled in our study. Results VTE was found in 120 of the 7,634 patients (1.57%), and the positive diagnosis rate of the 278 patients who underwent CTA was 43.2% (120 of 278). The incidence of VTE was statistically significantly higher among those with severe head and neck injuries (Abbreviated Injury Scale, 3–5) than among those with nonsevere head and neck injuries (Abbreviated Injury Scale, 0–2; P=0.038). In a subgroup analysis, the severe and nonsevere head and neck injury groups showed statistically significant differences in known independent risk factors for VTE. In logistic regression analysis, the adjusted odds ratio of severe head and neck injury (Abbreviated Injury Scale, 3–5) for VTE was 1.891 (95% confidence interval, 1.043–3.430). Conclusions Trauma patients with severe head and neck injuries are more susceptible to VTE than those with nonsevere head and neck injuries. Thus, physicians must consider CTA as a priority for the diagnosis of VTE in trauma patients with severe head and neck injuries who show VTE-associated symptoms.